Application of humic acid supplemented with micronutrient increase rice production - Siregar, Valdi Muhamad Rafiansyah; Soekarno Mismana Putra; Muhammad Abdul Aziz; Hana Fadila; Poppy Arisandy; Sri Wahyuni; Priyono; Insyiah Meida Luktyansyah; Sulastri; Rizky Nugraha; Mira Maulidina; Siswanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Fertilizer is one of the crucial inputs to maximize nutrients needed by plants, especially rice. However, insufficient ameliorant application may affect the fertilizers' effectiveness. Humic acid is believed as one of the ameliorants to improve soil conditions resulting in higher nutrient availability. The study aimed to evaluate the effect of combining humic acid and micronutrients on growth, production, and nutrient contents in rice. Three treatments were applied, i.e., control (without humic acid), humic acid, and humic acid + micronutrients. The result showed that both humic acid treatments produced the highest number of tillers, humic acid application solely stimulated the highest root length, and humic acid + micronutrients stimulated the highest plant height, and fresh and dry biomass weight. Grain weight was not affected by treatments, but humic acid + micronutrients gave a higher weight of milled grain and number of filled grains. Humic acid application solely resulted in plant biomass and grains having higher N, P, and K contents. Overall, the application of humic acid + micronutrients is recommended to increase rice production. Keywords: ameliorant; fertilizer; nutrient availability; nutrient uptake